Compensation for land rights holders according to the land acquisition law - Dhaniar Eka Budiastanti; Khotbatul Laila; Nahdiya Sabrina; Diah Aju Wisnuwardhani; Selvia Wisuda (Faculty of Law, University of Merdeka Malang, 2022)
The aspect of compensation is very crucial in land acquisition for development for the public interest. The Law of the Republic of Indonesia Number 2 of 2012 concerning Land Procurement for Development in the Public Interest (PTBPKU Law) is